Pengaruh Gaya Kepemimpinan dan Komitmen Terhadap Kinerja Karyawan dengan Kepuasan Kerja Sebagai Variabel Intervening pada Citra Mart - Hayatul Hafifa; Chintya Ones Charli; Minda Aulyani Ananda; Syifa Syai Ramadhani (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
The purpose of this study was to analyze the influence of leadership style and commitment on employee performance with job satisfaction as an intervening variable in the image of Mart with a sample of 1oo respondents. This type of research is explanatory research. The method used is data collection using questionnaires. PLS smart analysis method.